Kształtowanie cen dóbr medialnych - Żabiński, Ryszard (Shaping Prices of the Media Products and Services, 2008)
It can't be internal factors regarded as a point of reference for prices riding for manufacturer of media goods, but external factors. Internal factors should be only the basis of final calculation of prices. Arrangement of price should enable the company to cope with competition and should be acceptable by consumer. It is common phenomenon that companies wage price-war on the press market. Its essence is a long-lasting prices' reduction in order to eliminate of competition and gain the most market shares. This phenomenon is intensified particularly on printed press segment. Price-wars are applied within the confines of competitive areas grouping media goods(the media) from different segments of press market. Proper usage of price factor within the confines of segment requires qualification of the price sensibility rank in a segment. The dregs of liberty in riding the price of media goods can be defined by the usage of conception concerning product of many different characteristics with reference to media goods. The more the worth of particular product is perceived by consumers , the higher price can be used. Applying price-war is justified mostly with reference to media goods which are produced on a large scale; in situation when consumer is sensitive to price, when product is poorly distinguished and the intensity of competition in segment and competitive area is high.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 33, s. 151-164